2020
DOI: 10.1177/0363546520958697
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Soccer Players Undergoing Primary Hip Arthroscopy for Femoroacetabular Impingement: A Sex- and Competitive Level–Specific Analysis

Abstract: Background: Radiographic features of femoroacetabular impingement (FAI) are prevalent in kicking athletes, especially soccer players. However, there remains a paucity of data on the characteristics of symptomatic soccer players with an established diagnosis of FAI. Purpose: To report on patient demographics, injury, and clinical and radiographic characteristics in a large cohort of soccer players who underwent primary hip arthroscopy for FAI and to perform a sex- and competition level–specific analysis of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 32 publications
0
9
0
1
Order By: Relevance
“…Figure 1 shows a flowchart illustrating study screening and eligibility assessment. This process identified 23 studies, of which 6 were imaging diagnosis studies, 2 , 4 , 6 , 18 , 22 , 35 9 were prevalence studies, 2 , 5 , 21 , 23 – 25 , 27 , 32 , 33 9 reported outcomes after arthroscopic treatment, ∥ and 9 studies ¶ reported on adverse effects after arthroscopic treatment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 1 shows a flowchart illustrating study screening and eligibility assessment. This process identified 23 studies, of which 6 were imaging diagnosis studies, 2 , 4 , 6 , 18 , 22 , 35 9 were prevalence studies, 2 , 5 , 21 , 23 – 25 , 27 , 32 , 33 9 reported outcomes after arthroscopic treatment, ∥ and 9 studies ¶ reported on adverse effects after arthroscopic treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Table 2 shows a summary of the 9 studies 2 , 5 , 21 , 23 – 25 , 27 , 32 , 33 on the prevalence of AIIS impingement. Figure 2 shows the pooled prevalence of AIIS impingement in patients who underwent hip arthroscopy; there were no studies on prevalence in the general population.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical indicators from imaging include elevated alpha angle (measured > 50° on CT scans) and MRI evaluation of labral pathology. Imaging evaluation was performed as described by Marom et al [17].…”
Section: Methodsmentioning
confidence: 99%
“…Among the diferent sports, soccer has drawn increased interest with regard to FAIS, as it has been shown that soccer players have a higher prevalence of radiographic FAI morphology than athletes in other sports [11]. Additionally, the unique 1 3 sports-speciic characteristics and demands of playing soccer involves maneuvers which are comparable to maneuvers used to provoke FAIS [17].…”
Section: Introductionmentioning
confidence: 99%